An unidentified TeV source in the vicinity of Cygnus OB2 - Aharonian, Felix A.; Akhperjanian, A.; Beilicke, M.; Bernlöhr, Konrad; Hermann, G.; Heusler, A.; Hofmann, Werner; Horns, D.; Konopelko, Alexander; Krawczynski, Henric; Lampeitl, Hubert; Ona, E.; et al. (Astronomy and astrophysics, 2002)
Deep observation (~113 hrs) of the Cygnus region at TeV energies using the HEGRA stereoscopic system of air Čerenkov telescopes has serendipitously revealed a signal positionally inside the core of the OB association Cygnus OB2, at the edge of the 95% error circle of the EGRET source 3EG J2033+4118, and ~ north of Cyg X-3. The source centre of gravity is RA : , Dec : . The source is steady, has a post-trial significance of +4.6σ, indication for extension with radius at the ~ level, and has a differential power-law flux with hard photon index of . The integral flux above 1 TeV amounts ~3% that of the Crab. No counterpart for the TeV source at other wavelengths is presently identified, and its extension would disfavour an exclusive pulsar or AGN origin. If associated with Cygnus OB2, this dense concentration of young, massive stars provides an environment conducive to particle acceleration and likely subsequent interaction with a nearby gas cloud. Alternatively, one could envisage γ-ray production via a jet-driven termination shock.
Gesehen am 09.12.2020